Effect of Product Quality on Customer Satisfaction at Kopi Gowo Lippo Karawaci, Tangerang Selatan - Sembiring, Vienna Artina (Jurnal Penelitian Pariwisata, 2021)
This study aims to see the magnitude of the influence of product quality on customer satisfaction at Kopi Gowo Lippo Karawaci, South Tangerang. With the development of people's lifestyles, marketing orientation has changed. In addition, the development of the coffee business in South Tangerang causes a company to improve product quality to increase customer satisfaction. The researcher uses a simple regression analysis method with a quantitative descriptive approach, with a total of 97 consumers in Kopi Gowo Lippo Karawaci, South Tangerang. The results of this study indicate that product quality has a significant influence on customer satisfaction at Kopi Gowo Lippo Karawaci, South Tangerang because quality products have an important role in shaping customer satisfaction. The higher the quality of the product provided, the higher the satisfaction felt by the customer. When customer satisfaction is higher, it can lead to profits for the company. Kopi Gowo Lippo Karawaci, South Tangerang, should better prepare coffee drink products as a whole regarding the choice of coffee drink menu variants. Then the employees of Kopi Gowo Lippo Karawaci South Tangerang should further improve their skills in terms of speed, accuracy and become more responsive in serving consumers. Furthermore, Kopi Gowo Lippo Karawaci, South Tangerang, conducted a guest comment system, very helpful for the coffee shop to further improve the quality of coffee drinks. Keywords: Product Quality, Customer Satisfaction